Planning for wind power as a basis for multifunctional landscape design - Öhrström, Sanne (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2013)
Wind power is a growing industry, which has an increasing impact on our landscapes. Many articles and papers have been published about public acceptance and the importance to consider the wider landscape when placing turbines. Surprisingly though is the lacking of wind power integration research – not visually, but functionally. This work and analysis has identified processes and working tools which should be incorporated in the planning procedure. Having wind power as a backbone landscape design becomes most interesting. There are many limiting regulations to consider, often leading to a negative planning approach today, where a design study may give new views to approach specific projects.